Metaphorical Reference and the Existence of God - Miller, Adam S. (Horizons, 2005)
The advent of science has dislocated God from the ontological heart of the world. God no longer anchors, nor defines our shared horizons. As a result, the question of God's literal existence is no longer primary. Nonetheless, the question of God is no more avoidable than it has ever been. God continues to ceaselessly intervene in our lives in the form of the question: what do you love? To address the question of God in our world is to address the question of love and love's object. In particular, it is to address the question of love's mode of reference. Love's mode of reference, when properly understood, is metaphor, and to understand how it is possible for metaphor to refer is to have our understanding of existence and literality transformed.